Elementary School Students' Problem Solving Strategies in Adding and Subtracting Whole Numbers Through Open Ended Problems - Anggi Umayrah; Tatang Herman; Al Jupri; Syifa Salsabila (PAEDAGOGIA, 2025)
Problem-solving skills are an important aspect of mathematics learning that needs to be developed from elementary school. One way to stimulate this ability is through open-ended problems that allow students to express a variety of solution strategies. This study aims to analyze problem-solving strategies and difficulties experienced by grade IV elementary school students in solving story problems of addition and subtraction of whole number with an open approach. The research method used is qualitative with a case study design. The research subjects were grade IV students who were given validated open-ended story questions. Data were collected through learning observation and analyzed descriptively. The results showed that students used different strategies, such as gradually summing, reducing the remaining capacity, and combining the total number with the bus capacity. However, errors in place values, procedural errors, and lack of thoroughness were also found. These findings confirm that open-ended questions are effective in practicing problem-solving as well as exposing students' misconceptions